133P Tumour immune infiltrate characterization in luminal breast cancer in three distinct age categories and its correlation with frailty. (15th December 2019) - Berben, L; Wildiers, H; Kenis, C; Dalmasso, B; Smeets, A; Vos, H; Neven, P; Floris, G; Hatse, S
Abstract: Background: Immunosenescence, the age-related decrease in immune competence, is characterized by decreased adaptive immunity and increased low-grade inflammation. This may lead to altered anti-tumor immune responses and thus affect tumor immune infiltrate in older patients with cancer. However, detailed tumor infiltrate characterization in breast cancer (BC) has not yet been performed in the context of aging. Methods: This exploratory study investigated age-related changes in the tumor microenvironment of patients with early BC (grade I-III, ER+, HER2-). Patients were subdivided into three age categories: 35-45 years (y) (N = 15), 55-65y (N = 19), ≥70y (N = 31). Stromal tumor infiltrating lymphocytes (sTILs) percentage was assessed following published guidelines. Immune infiltrate characterization was established by determining CD68 grade and scoring additional immune markers (CD3, CD4, CD5, CD8, CD20 and FOXP3) with a newly developed analysis pipeline using the QuPath software. In the oldest group, the geriatric 8 (G8) score was obtained as a correlate for clinical frailty level. Results: With increasing age, sTILs percentage significantly decreased, concomitant with significantly lower Tcells (CD3 + and CD5 + ), cytotoxic Tcells (CD8 + ) and Bcells (CD20 + ) densities in the whole tumor area. When assessing tumor regions separately, significant age-related decreases in immune cell density in invasive front (CD3 +, CD5 +, CD8 +, CD20 + cells) and tumor center (CD3 +, CD5 +, CD8 + cells) were observed. No age-related changes were seen for CD4 + and FOXP3 + cell infiltration nor for CD68 grade in the tumor. G8 score showed a significant inverse correlation with regulatory Tcells (FOXP3 + ) density in tumor center. However, spatial distribution of the immune cell populations did not depend on age nor frailty level. Conclusion: In conclusion, sTILs percentage and density of several immune markers in the tumor significantly differed between young and older patients with BC. Moreover, density of regulatory T-cells was higher in frailer patients (lower G8 score). This may indicate that tumor immune responses in these patients may be less effective, and approaches for immunotherapy may vary depending on patients' age/frailty level. Legal entity responsible for the study: Hans Wildiers. Funding: FWO. Disclosure: All authors have declared no conflicts of interest.